Determining the Laurentide Ice Sheet and Bedrock Provenance of Midwestern Till by Applying U-Pb Geochronology to Detrital Zircons - Mickey, Jeremiah Lee (2019)
Indiana University-Purdue University Indianapolis (IUPUI) A broad range of samples were collected from the Huron-Erie Lobe, Lake Michigan Lobe, Saginaw Lobe, and Tipton Till Plain of northern Indiana to determine the provenance of Laurentide Ice Sheet till in the Midwest U.S. during the Illinoian and Wisconsinan glaciations. U-Pb age distributions from approximately 300 detrital zircons (DZ) were used as provenance indicators for each till sample. Till from the Lake Michigan Lobe and was found to be largely homogenized. The distinct lobe DZ age distributions are the Lake Michigan Lobe till with a dominant ~1465 Ma peak, the northern Huron-Erie Lobe till with a dominant ~1060 Ma and a secondary peak at ~1450 Ma, the southern Huron-Erie Lobe till with nearly equal peaks at ~1435 Ma, ~1175 Ma, and ~1065 Ma, and the southern Saginaw Lobe till with a dominant peak at ~1095 Ma. Those four DZ age distributions were treated as endmembers in a nonlinear least-squares mixing model to calculate the contribution of each lobe to till in the Tipton Till Plain. Huron-Erie and Saginaw lobe tills were found to be the primary components of the Tipton Till Plain, and Lake Michigan Lobe till was only found in the western Tipton Till Plain. Zircons from the Saginaw Lobe till increased 39 % in the eastern Tipton Till Plain between the Illinoisan and Wisconsinan glaciations. The mixing model was also applied to relate the DZ age distributions of the lobes to bedrock within and near their flow paths. When comparing nearby bedrock to each lobe’s till, mixing model results, yield an approximate maximum transport distance between 500 and 630 kilometers for the matrix vii fraction of till in the Lake Michigan, Huron-Erie, and Saginaw lobes. Samples for the southern Huron-Erie Lobe indicate that the most of the zircon ages within the southern Huron-Erie Lobe till in Indiana were specifically entrained between Niagara County, New York and east-central Indiana. Within the model’s error, 93 – 100 % of the detrital zircons in each of the ...